Perancangan Sistem Manajemen Surat dan Validasi Dokumen dengan Fitur Tanda Tangan Elektronik di STT Terpadu Nurul Fikri - Edi Wibowo; Annisa Nasywa Salsabila; Mira Sonnia Alodia (Pusat riset dan Inovasi Nasional, 2025)
Mail management in higher education institutions, particularly at the Nurul Fikri Integrated Technology College (STT), is still carried out manually or conventionally. This process involves physically recording and distributing letters, which in practice often creates various obstacles. Some common obstacles include the long time required to manage letters, the risk of document loss or damage, and the high possibility of errors in letter numbering. Furthermore, the document validation process is also less effective due to the lack of a system that supports electronic signatures or digital verification of document authenticity. Based on these conditions, this study aims to design and develop a digital system that can help manage letters more efficiently and securely. This system is designed not only to speed up the administrative flow of correspondence but also to simplify the document validation process through the application of digital technology. Thus, this system is expected to reduce administrative errors, increase work efficiency, and ensure the security and validity of official documents. The method used in this study is Design Thinking, which consists of five main stages: empathize, define, ideate, prototype, and test. This approach enabled researchers to deeply understand user needs, explore various alternative solutions, and create an intuitive and user-friendly interface design for all parties involved in the administrative process. The research results showed that the designed system can accelerate the administration process for official letters and documents. The embedded superior features include digital validation and electronic signatures integrated with QR Code technology, thus providing a higher level of transparency and security in document management within the university environment.